Islamic State of Afghanistan : Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2004)
Since end-2001, the Government of Afghanistan (GoA) has focused on crisis management, establishing or rebuilding fundamental institutions and basic government services, and maintaining economic stability with the help of the international community. The authorities have made significant strides in fiscal and monetary policies. The new constitution, adopted by the Loya Jirga and signed into law in January 2004, is a critical step to re-establish a unified state and strengthen the institutional framework. The authorities recognize that the domestic revenue target included in the 2004/05 operating budget is very ambitious.